Utilization of Postnatal Care Services among Women of Urban Slums - Shruti Kardalkar; Mayur S Sherkhane (Medsci Publications, 2018)
Background: Utilization of postnatal services is the right of every woman and can be affected by socio-demographic factors and in turn with the availability of services. This research was undertaken to study the pattern of utilization of postnatal care services and factors affecting it among postnatal women of urban slums Methods: Cross sectional study was done and data was collected by house to house survey after taking consent, using a pre- designed and pre-tested proforma. Results: Majority 54.21% women belonged to 21-25years of age, 56.84% were educated till high school and 88.95% belonged to lower class. 69.47% and 21.58% utilized ANC and PNC services. Literates and primi mothers had utilized PNC services compared to illiterates and multipara. Lower socioeconomic status women had used PNC adequately when compared to higher  class (p<0.05). Conclusion: Knowledge about PNC visits was good but the utili- zation of PNC package was less compared to ANC. Health educa- tion should be imparted at all levels of the healthcare to give mother and child a safe future.